2011
DOI: 10.1007/s11164-011-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant, antimicrobial evaluation, DFT studies of novel metal complexes derivate from Schiff base

Abstract: In Iraq, like most developing countries, attempts are being made to synthesize new compounds with several pharmacological properties. (E)-2-(3-(2-imino-1-methylimidazolidin-4-ylidene)-1-methylguanidino)acetic acid (L) has been synthesized and used as a ligand for the formation of Cr(III), Co(II), Ni(II), and Cu(II) complexes. The chemical structures of synthesized compounds were characterized using different spectroscopic methods. All chelates except Ni(II) chelate are found to be octahedral structures, Ni(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…However, the working principles of this approach are not yet fully understood [15]. In the continuation of previous studies [16][17][18][19][20][21][22][23], we focused on the photostabilization of PVC using 1,3,4-thiadiazole compounds. To our knowledge, there has been no attempt to investigate the photostabilization of PVC films by Schiff bases containing four 1,3,4-thiadiazole rings; therefore, in this study, we report the design of the Schiff bases and the study of their use as a photostabilizing reagents.…”
Section: Introductionmentioning
confidence: 99%
“…However, the working principles of this approach are not yet fully understood [15]. In the continuation of previous studies [16][17][18][19][20][21][22][23], we focused on the photostabilization of PVC using 1,3,4-thiadiazole compounds. To our knowledge, there has been no attempt to investigate the photostabilization of PVC films by Schiff bases containing four 1,3,4-thiadiazole rings; therefore, in this study, we report the design of the Schiff bases and the study of their use as a photostabilizing reagents.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study [34] has shown that atomic charges were affected by the presence of the substituent of rings. For compound 3 the 3D geometrical structure is given in Figure 1 …”
Section: Atomic Charges (Mulliken Chargesmentioning
confidence: 97%
“…The B3LYP density functional theory calculations exhibit good performance on the molecular geometry and vibrational properties of organic compounds 8,9 . To extend our studies on the design and synthesis of new compounds [10][11][12][13][14][15][16][17][18][19][20][21][22] , we describe here, investigate the dependence of stability of the molecules on theoretical chemical parameters such as total energy, energy level of (HOMO), and energy gap. We have three stable molecules, HQ-7-YBAEE (II) for the total energy, HQ-6-YBAEE (II) for the energy level of (HOMO) and HQ-2-YBAEE (II) for the energy gap.…”
Section: Introductionmentioning
confidence: 99%